Factor Strategy Model: Proofs of Prototype Concept for Software Quality Evaluation - Nathan, Darmawan; Ooi, Keng Boon; Chong, Alain Yee Loong; Tan, Boon In (Taylor & Francis, 2010)
The objective of this study is to provide software developers some measures to evaluate software quality of a Java program. Studies on software quality requirements, software quality models (as a quantifying measurement technique) and various good design rules are required for. This study aims to solve the problem for software developers or students having difficulty to identify the bad software design in their software product. Thus, by providing an algorithm analyzer to analyze the quality of design of the software product, developers or students can identify possible bad software design in their application.